Exercise on Prescription. Effect of attendance on participants' psychological factors in a Danish version of Exercise on Prescription: A Study Protocol - Roessler Kirsten K; Puggaard Lis; Bredahl Thomas VG (BMC, 2008)
Abstract Background In many countries exercise prescriptions are used to facilitate physical activity in a sedentary population with or in risk of developing lifestyle diseases. Some studies show a positive effect of exercise prescription on specific lifestyle diseases. Others only show moderately positive or no effect on physical activity level. Furthermore, the challenge is adherence of participants to a physically active lifestyle on a long term basis after intervention. Therefore, it is essential for offering successful prescribed interventions aiming towards behaviour change to focus on psychological and social issues as well as physiological issues. The aim of this study is to assess the short and long term development of psychological conditions in two different Exercise on Prescription groups; The Treatment Perspective and The Preventive Perspective behaviour. Thus, the aim of this paper is to describe the design used. Methods/Design The Treatment Perspective involves a 16 week supervised training intervention including motivational counselling. The Preventive Perspective only involves motivational counselling. The study is an evaluation of best practice and is accomplished by the use of a combination of quantitative (collected by questionnaires) and qualitative (collected by the use of semi structured interviews) measures. Comparison of The Treatment Perspective and The Preventive Perspective are performed at baseline and after 16 months. Development within the groups is measured at 4, 10, and 16 months. Self-reported measures describe physical activity, health-related quality of life, compliance with national guidelines for physical activity, physical fitness, self-efficacy, readiness to change, decisional balance, and processes of change. To elaborate self-efficacy, readiness to change, decisional balance, and processes of change, these issues were elucidated by interviews. Discussion This study of best practice is designed to provide information about important psychological concepts in relation to behaviour change and physical activity. The study is part of a health technology assessment of Exercise on Prescription, which apart from the psychological concepts (the patient's perspective) covers the effectiveness, the organization, and the health economy.